2018
DOI: 10.20855/ijav.2018.23.21450
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on a Kinetic Theoretical Model of the Straight-Curved Pipe Conveying Fluid

Abstract: A kinetic theoretical model for the straight-curved pipe conveying fluid was proposed and studied in this paper. Firstly, the new equations of static equilibrium and motion about equilibrium position were derived by applying perturbation method to the motion equations of the curved pipe conveying fluid. Then, the kinetic equations of the straight pipe were derived by ignoring the terms containing the curvature of the curved pipe in these equations. Subsequently, considering different factors, four segmental ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In addition, it was found that the steady combined force could have a great impact on the vibration characteristics of the curved-shaped pipe. As pointed out by Wen et al [40], the nonlinear force caused by the deformation of the straight pipe segment, static deformation and geometrical non-linearity of the pipe could have a considerable influence on the dynamics of the straight-curved combination pipe. Unfortunately, this effect was not taken into account in the study of Koo and Yoo [36], and only the static axial force caused by static deformation of the pipe was contained in the Dai et al's model [38].…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…In addition, it was found that the steady combined force could have a great impact on the vibration characteristics of the curved-shaped pipe. As pointed out by Wen et al [40], the nonlinear force caused by the deformation of the straight pipe segment, static deformation and geometrical non-linearity of the pipe could have a considerable influence on the dynamics of the straight-curved combination pipe. Unfortunately, this effect was not taken into account in the study of Koo and Yoo [36], and only the static axial force caused by static deformation of the pipe was contained in the Dai et al's model [38].…”
Section: Introductionmentioning
confidence: 96%
“…Thus, it is worth to explore the dynamics of the straight-curved combination fluid-conveying pipe. Indeed, a few researchers have studied this kind of pipe [34][35][36][37][38][39][40][41][42][43]. In 1990, a linear analytical model that include the Poisson coupling was proposed by Lesmez et al [34] to perform the modal analysis of vibrations in liquid-filled piping system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Doll and Mote Jr [15] presented dynamical curved and twisted pipes to conclusion proved to be comparable. Wen and Yang [16] and Morad [17] investigated the pipe included in a direct section associated to a curved section. The conservatory of the pipe axis was suitably accounted for and natural frequencies of the system which they found to be slightly responsive to fluid flow velocity variations.…”
Section: Introductionmentioning
confidence: 99%